Implementation of Corporate Social Responsibility as a Legal Mandatory in Indonesia (Case Study of PT AFC Indonesia) - Irfandy H Simanungkalit; Martono Anggusti; Ria Juliana Siregar (Journal of Law, Politic and Humanities, 2025)
This study examines PT AFC Indonesia and how companies should implement Corporate Social Responsibility (CSR) as a legal mandatory in Indonesia. Law No. 40 of 2007 regulates CSR as a moral responsibility. The purpose of this study is to evaluate how PT AFC Indonesia implements CSR and make recommendations for other companies. A qualitative method was used, which was used to analyze documents and interviews. The results show that PT AFC Indonesia improves the quality of life of the community through CSR programs that improve health services, clean water supply, and educational support. The conclusion is that this CSR implementation enhances the company's reputation and supports sustainable development in Indonesia.